Associations between demographic and disease related factors and anxiety and depression among adolescents with chronic kidney disease - Bai, Changchang; Wei, Mingjie; Huang, Shuli; Fu, Junmei; Ning, Guigui; Zhai, Wensheng (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the current status of comorbid anxiety and depression in adolescents with chronic kidney disease and to analyze their associated factors.Methods105 adolescents with chronic kidney disease, hospitalized in the First Affiliated Hospital of Henan University of Traditional Chinese Medicine from May 2022 to May 2023, were selected through convenience sampling. A general information questionnaire, anxiety self-assessment scale, and depression self-assessment scale were used. Factors associated with anxiety and depression were analyzed using univariate analysis, and significant variables underwent multinomial logistic regression.ResultsAmong the 105 adolescents, 11 cases (10.5%) had anxiety alone, 6 cases (5.7%) had depression alone, and 26 cases (24.8%) presented both anxiety and depression. Multinomia logistic regression analysis revealed that the illness duration (>12 months) (OR = 34.114), duration of hormone treatment (≥12 months) (OR = 37.585), duration of immunotherapy (≥12 months) (OR = 12.700), and OR values greater than 1 indicate that illness duration (>12 months), duration of hormone treatment (≥12 months), and the duration of immunotherapy (≥12 months) are independent associated factors for nanxiety and depression.ConclusionIn this cross-sectional cohort study, the illness duration, duration of hormone treatment and duration of immunotherapy are independent associated factors for anxiety and depression. Psychological screening should be prioritized for adolescents with these clinical features, and relevant measures should be taken to reduce the incidence of anxiety and depression in adolescents with CKD. Future longitudinal studies could begin by elucidating whether modifying treatment can reduce mental health risks, taking into account potential bidirectional effects between disease control and mental health.